Experimental Forest: Notes Toward an Installation - Wolfe, Cary (Identities: Journal for Politics, Gender and Culture, 2022)
Author(s): Cary Wolfe Title (English): Experimental Forest: Notes Toward an Installation Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 72-91 Page Count: 19 Citation (English): Cary Wolfe, “Experimental Forest: Notes Toward an Installation,” Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022): 72-91. Author Biography Cary Wolfe, Rice University Cary Wolfe is Bruce and Elizabeth Dunlevie Professor of English at Rice University, where he is Founding Director of 3CT: Center for Critical and Cultural Theory. His books and edited collections include Animal Rites: American Culture, The Discourse of Species, and Posthumanist Theory (Chicago, 2003), Zoontologies: The Question of the Animal (Minnesota, 2003) What Is Posthumanism? (Minnesota, 2010), Before the Law: Humans and Other Animals in a Biopolitical Frame (Chi[1]cago, 2012) and, most recently, Ecological Poetics, or, Wallace Stevens’s Birds (Chicago, 2020) and Art and Posthumanism: Essays, Encounters, Conversations (Minnesota, 2021). In 2007 he founded the series Posthumanities at the University of Minnesota Press, which has published more than sixty-five volumes to date by noted authors such as Donna Haraway, Roberto Esposito, Isabelle Stengers, Michel Serres, Vilem Flusser, Jacques Derrida, Vinciane Despret, and others.